Paper, color, line : European master drawings from the Wadsworth Atheneum - Tostmann, Oliver (Wadsworth Atheneum Museum of Art in association with Paul Holberton Publishing, 2025)
"The Wadsworth Atheneum Museum of Art's rich collection of European drawings, watercolors and pastels is little-known and rarely seen. Since the mid-nineteenth century, the museum has acquired by purchase and gift a diverse group of nearly 1,250 European drawings of impressive quality. Paper, Color, Line: European Master Drawings from the Wadsworth Atheneum showcases some sixty highlights from the collection. Published on the occasion of an exhibition, this long-overdue catalogue is a unique survey of artists working in drawing media over a span of more than five hundred years. The museum's holdings are particularly strong in works from the nineteenth and twentieth centuries. Renowned drawings by Gustave Courbet, Edgar Degas and Henri de Toulouse-Lautrec are included, as well as highlights by Egon Schiele, Paul Klee and Joan Miró. The collection is distinguished by its theatrical designs, particularly those linked with the Ballets Russes, with contributions by Pablo Picasso, Léon Bakst and Natalia Goncharova. Significant works from the Renaissance to the Rococo by artists such as Giorgio Vasari, Carlo Maratti and Jean-Baptiste Greuze emphasize the timeless appeal of drawing and will complement the overview. The catalogue of the exhibition will be the first catalog devoted to European drawings at the Wadsworth Atheneum. It will present fresh research on the objects as well as on the history of collecting European drawings at the museum"--